PHYTOCHEMICAL ANALYSIS AND ANTIOXIDANT ACTIVITY OF PURNAJIWA FRUIT EXTRACT (Euchresta horsfieldii (Lesch.) Benn.) - Romulia Trielva Apriliani; I Gede Putu Wirawan; Wayan Adiartayasa (Central Laboratory for Genetic Resource and Molecular Biology, Faculty of Agriculture, Udayana University in cooperation with Asia-Oceania Bioscience and Biotechnology Consortium (AOBBC), 2020)
Antioxidant is a chemical compound that could give one or more electrons to inhibit the free radical reaction. One of the plants that potentially produce antioxidants is purnajiwa (Euchresta horsfieldii (Lesch.) Benn.). The research was conducted using the fruit of purnajiwa. The purpose of this study is to know antioxidant activity from purnajiwa fruit using the DPPH method and measured by UV-Vis spectrophotometry. The extract of purnajiwa fruit gained by the maceration method using 96% ethanol solvent. The results of phytochemistry screening found out that the extract contains flavonoid, alkaloid, saponin, tannin, and terpenoid. According to flavonoid testing using quercetin, the results obtained from purnajiwa extract contained flavonoid of 1,651 mg QE/g. The activity test of antioxidants quantitatively by DPPH using UV-Vis spectrophotometry found out that purnajiwa extract has IC50 value of 57,28 ppm so that purnajiwa extract has strong antioxidant activity that could be used as natural antioxidant resources.